THE DRAWBACK AS MECHANISM PROMOTION OF EXPORTATION. HOW IMPROVE THEIR IMPACT IN THE MYPE? - Flores Konja, Adrián Alejandro (2009)
This article shows the leading features of “drawback”, or Restitution of tariffs, customs regime of exportations promotion, established in support of exporters companies, communicating about the regime’s advantages, their conditions and requirements, and formal procedures to obtain it. Show some definitions about their character, its macroeconomics importance, als support mechanisms to Micro and small enterprises (MYP E, in Spanish) and its internationalization, and question: Why “drawback” wasn’t more efficient supporting micro and small exporters enterprises? Show the problems of applications of “drawback” by Micro and small enterprises and analyze some statements of associations of exporters and experts. The article proposes some conclusions, that need attention of researchers of the area of enterprise sciences, specially, accountants. The preliminary research was basically descriptive, and was a documentary analysis of regulations, law and taxation doctrine and differents statements about the matter of associations of MYP E. We’ll make later the field research, applying surveys, interviews and “focus groups”. As a result of that preliminary research, we conclude that MYP E didn’t use “drawback” like a truly incentive for internationalization. Between the immediate causes of that situations, that was provisionally established, the directors of MYP E don’t know the benefits of drawback, that MYP E don’t have trained personnel for applying “drawback”. Also, the requirements to apply the regimen can be, in most cases, out of the reach of MYP E; and the mulets for a wrong applications of “drawback” are so high and out of proportions, that discourage MYP E to applied that regime.